Knowledge, attitude, and practice of cardiac rehabilitation among patients after coronary artery stenting - Xiaochen Tian; Tao Han; Fanli Bu; Jing Li; Lin Hao; Leisheng Zhang; Ping Lu (Scientific Reports)
Abstract Stent implantation effectively relieves coronary artery disease (CAD), and post-surgery cardiac rehabilitation is essential for prognosis. This study aimed to investigate the knowledge, attitude, and practice (KAP) of patients undergoing coronary artery stenting regarding cardiac rehabilitation. Conducted in multiple hospitals from December 2023 to January 2024, a self-administered questionnaire collected demographic information and KAP scores. A total of 452 valid subjects were included, with 262 participating in cardiac rehabilitation. The average age was 56.76 ± 12.97 years, with 57.52% male and 72.35% urban residents. Mean KAP scores were 14.63 ± 4.70 (knowledge), 37.50 ± 4.15 (attitude), and 30.96 ± 4.49 (practice). Positive correlations were found between KAP scores (r = 0.378–0.474, P < 0.001). Urban residence, angina, and myocardial infarction diagnoses were positively associated with knowledge (OR = 1.881–3.192, P < 0.05). Conversely, medical insurance, continued drinking post-implantation, and other underlying diseases were negatively associated (OR = 0.193–0.592, P < 0.05). Myocardial infarction diagnosis (OR = 2.059, P = 0.026) and health education (OR = 1.830, P = 0.018) positively influenced attitudes. Medical insurance was associated with practice (OR = 4.567, P = 0.028). Patients showed moderate knowledge and positive attitudes towards cardiac rehabilitation, highlighting the need for educational interventions for rural residents and individuals who did not initiate rehabilitation.